Hypothalamic obesity in children - (:unkn) unknown (WILEY, 2012)
Hypothalamic obesity is an intractable form of obesity syndrome that was initially described in patients with hypothalamic tumours and surgical damage. However, this definition is now expanded to include obesity developing after a variety of insults, including intracranial infections, infiltrations, trauma, vascular problems and hydrocephalus, in addition to acquired or congenital functional defects in central energy homeostasis in children with the so-called common obesity. The pathogenetic mechanisms underlying hypothalamic obesity are complex and multifactorial. Weight gain results from damage to the ventromedial hypothalamus, which leads, variously, to hyperphagia, a low-resting metabolic rate; autonomic imbalance; growth hormone-, gonadotropins and thyroid-stimulating hormone deficiency; hypomobility; and insomnia. Hypothalamic obesity did not receive enough attention, as evidenced by rarity of studies in this group of patients. A satellite symposium was held during the European Congress of Obesity in May 2011, in Istanbul, Turkey, to discuss recent developments and concepts regarding pathophysiology and management of hypothalamic obesity in children. An international group of leading researchers presented certain aspects of the problem. This paper summarizes the highlights of this symposium. Understanding the central role of the hypothalamus in the regulation of feeding and energy metabolism will help us gain insights into the pathogenesis and management of common obesity.
Keywords: Craniopharyngioma; hypothalamic; obesity; Prader-Willi syndrome; PRADER-WILLI-SYNDROME; BODY-MASS INDEX; INCREASED DAYTIME SLEEPINESS; TRIAL KRANIOPHARYNGEOM 2000; FASTING PLASMA GHRELIN; HISTAMINE H-1 RECEPTOR; INDUCED WEIGHT-GAIN; CHILDHOOD CRANIOPHARYNGIOMA; BARIATRIC SURGERY; SLEEVE GASTRECTOMY